"Why aren't you a Muslim?"Pride and prejudice through Gunawan Mahmood's teen fiction - Lim, David C. L. (Brill, 2008)
This essay examines the role of the dominant Malay intelligentsia in imagining Malaysia, using as platform for discussion two contemporary teen novels by Gunawan Mahmood: This Land (originally published in Malay as Tanah Ini in 1996; out in English translation in 2002) and Namaku Ayoko (My Name is Ayoko; 1994). The chosen author and texts are little known outside of the Malay literary world, which alters not the fact that Gunawan is a multiple award-winning, state-affiliated writer who, like many of his Malay-Muslim contemporaries and predecessors, believes that “those with knowledge ought to write” and “literature should educate, awaken and inspire society” (in Mahmood, 1993:x). Gunawan is an ‘intellectual’ insofar as he participates in the production and distribution of knowledge, as someone who professes a vocation for the art of “representing, embodying, articulating a message, a view, an attitude, philosophy or opinion to, as well as for, a public” (Said, 1996:11). (Text by author)